2015
DOI: 10.1002/qj.2660
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the sea state on Mediterranean heavy precipitation: a case‐study from HyMeX SOP1

Abstract: Sea state can influence the turbulent air–sea exchanges, especially the momentum flux, by modifying the sea‐surface roughness. The high‐resolution non‐hydrostatic convection‐permitting model MESO‐NH is used here to investigate the impact of a more realistic representation of the waves on heavy precipitation during the Intense Observation Period (IOP) 16a of the first HyMeX Special Observation Period (SOP1). Several quasi‐stationary mesoscale convective systems developed over the western Mediterranean region, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 44 publications
5
39
2
Order By: Relevance
“…(2). This result is in agreement with the findings of Thévenot et al (2015), who showed that an increase in wave height (and a resulting increase in z 0 ) leads to lower wind speeds.…”
Section: Discussionsupporting
confidence: 93%
“…(2). This result is in agreement with the findings of Thévenot et al (2015), who showed that an increase in wave height (and a resulting increase in z 0 ) leads to lower wind speeds.…”
Section: Discussionsupporting
confidence: 93%
“…A further step towards operational real‐time forecasts would be to explore strategies for combining ocean data assimilation and atmosphere data assimilation for the AROME‐NEMO system. Another perspective is to take into account the sea state with the introduction of a wave model into the coupled system, as waves strongly impact the sea surface turbulent fluxes and thus can significantly modify the weather forecast (Renault et al , 2012; Ricchi et al , 2016; Thévenot et al , 2016; Bouin et al , 2017; Voldoire et al , 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Two case‐studies have been chosen from the HyMeX SOP1 period because they include the two kinds of intense weather events of interest: first a moderate mistral episode followed by an HPE during IOP13 (Rainaud et al , 2016), and secondly, an HPE followed by a severe mistral event during IOP16a/b (Ducrocq et al , 2014; Duffourg et al , 2016). Moreover, for these two IOPs, it has been suggested that air–sea exchanges played a significant role (Rainaud et al , 2016; Thévenot et al , 2016). A brief description of the events is given in the following.…”
Section: Case‐studiesmentioning
confidence: 99%
“…Other studies have shown that the simulation of the convective system is very sensitive to model parametrizations. For example, Thévenot et al () also shows for this IOP how the turbulent air–sea exchanges can modify the low‐level dynamics of the atmosphere and the precipitation location. In Rainaud (), a change in the sea surface temperature or the coupling of the atmosphere with an oceanic model is found to have a large impact on the simulated precipitation amount overland.…”
Section: Summary and Outlooksmentioning
confidence: 99%